What aspects of the home literacy environment differentiate Chinese children at risk for reading difficulties from their not at risk controls? - Zhang, Su Zhen; Georgiou, George K.; Shu, Hua (Preschool and Primary Education, 2019)
We examined what aspects of the home literacy environment (formal home literacy activities, informal home literacy activities, access to literacy resources, age of onset of literacy instruction, child’s interest in reading, and parents’ expectations) differentiate Chinese children at risk for reading difficulties from their not-at-risk controls. Eighteen children from Jining, China, who were at risk for reading difficulties and 32 not-at-risk controls participated in the study. Their parents also participated in the study by filling out a home literacy questionnaire, by recording the daily parent-child reading activities (diary), and by completing the Children’s Title Recognition Checklist. Group comparisons revealed significant differences only in items measuring children’s access to literacy resources and reading interest. Results of discriminant function analyses further showed that the home literacy environment variables could discriminate well between the children at risk for reading difficulties and their controls. Taken together, our findings suggest that to the extent environment plays a role in reading difficulties in Chinese, this should be traced to factors such as child’s interest in reading and access to literacy resources.